2018
DOI: 10.3390/molecules23010215
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates on Carbon Tetrachloride-Induced Acute Liver Injury in Mice via Modulation of the Nrf2/HO-1 and TGF-β1/Smad3 Pathway

Abstract: This study aimed to investigate the protective effect of curcumin against carbon tetrachloride (CCl4)-induced acute liver injury in a mouse model, and to explain the underlying mechanism. Curcumin at doses of 50, 100 and 200 mg/kg/day were administered orally once daily for seven days prior to CCl4 exposure. At 24 h, curcumin-attenuated CCl4 induced elevated serum transaminase activities and histopathological damage in the mouse’s liver. Curcumin pre-treatment at 50, 100 and 200 mg/kg significantly ameliorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 57 publications
5
65
0
Order By: Relevance
“…Binding to the heterodimer recognizes and binds ARE, initiates transcription of the downstream protective protein genes, and enhances cell's ability to resist oxidative stress (McMahon et al, 2006). Nrf2 signaling may compensatorily increase the response to acute stress (Stewart et al, 2003), modulating expression of several oxidative damage genes, including HO-1 and SOD2 that are protective in diverse models of liver diseases (Ge et al, 2015;Peng et al, 2018). In our study, diabetes markedly resulted in down-regulation of Nrf2, HO-1 and SOD2, an effect that was reversed by FGF1 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding to the heterodimer recognizes and binds ARE, initiates transcription of the downstream protective protein genes, and enhances cell's ability to resist oxidative stress (McMahon et al, 2006). Nrf2 signaling may compensatorily increase the response to acute stress (Stewart et al, 2003), modulating expression of several oxidative damage genes, including HO-1 and SOD2 that are protective in diverse models of liver diseases (Ge et al, 2015;Peng et al, 2018). In our study, diabetes markedly resulted in down-regulation of Nrf2, HO-1 and SOD2, an effect that was reversed by FGF1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that ER stress induced the production of reactive oxygen species (ROS) (Peng et al, 2018), thereby leading to oxidative stress (Hyung-Ryong et al, 2009). ER stress occurs when misfolded proteins accumulate in the ER lumen, and this is referred to as the unfolded protein response (UPR) (Hyung-Ryong et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf-2 is a transcription factor that eliminates ROS (7) products by increasing the antioxidant enzymes (DeNicola et al, 2011). As a result, curcumin activates the expression of Nrf-2, thus protecting the cells against oxidative stress damage and by regulating the genes that contain antioxidant enzymes (Peng, Dai, Liu, Li, & Qiu, 2018) heme oxygenase (HO)-1 and NAD(P)H:quinone oxidoreductase 1 (NQO1) (Shehzad & Lee, 2013) and prevents lipid peroxidation (Deogade & Ghate, 2015), thereby reducing the damage caused by oxidative stress in sepsis 4.6 | Effect of curcumin on immune response…”
Section: The Effects Of Curcumin On Oxidative Stressmentioning
confidence: 99%
“…have been considered to contribute to the pathogenesis and progression of this disorder [ 13 , 14 ]. It is well-known that carbon tetrachloride (CCl 4 )-induced acute liver injury model shares a similar molecular mechanism with acute chemical liver injury in humans [ 15 ]. Especially, oxidative stress, inflammation response, and apoptosis have been recognized as the most important pathomechanisms during the progress of CCl 4 -induced acute liver injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%